Corporate Social Responsibility, Employee Welfare and Social Return on Investment - Pranata, Natasha Anjanette; Batuwael, Marcelia Adriana; Mahmud, M. Riza; Handoko, Steven Nathanael; Wicaksono, Septia; Pandin, Maria Yovita R. (Universitas Bhayangkara Surabaya, 2025)
Corporate Social Responsibility (CSR) has become a major focus in the business world, as companies are not only required to achieve profits, but also contribute socially to society and the environment. This study aims to analyze the relationship between CSR implementation and community welfare on Social Return On Investment (SROI) with the case of PT Astra International Tbk during the 2020-2024 period. This research method uses a quantitative approach that utilizes secondary data from the company's sustainability report, while the data analysis is carried out with the help of SPSS. The research findings show that CSR and employee welfare partially or simultaneously have no significant influence on SROI. The study suggests that future research should increase the amount of data, determine other relevant variables, and handle multicollinearity to get more precise results.